2021
DOI: 10.3389/fimmu.2021.650979
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polymorphisms in T-Cell Activation Costimulatory/Inhibitory Signal Genes With Allograft Kidney Rejection Risk

Abstract: The genes CD28, CD86 and CTLA-4 conform the costimulatory (CD28-CD86) or inhibitory (CTLA-4-CD86) signal in T-cell activation. T-cell immune response has a critical role in allograft rejection, and single nucleotide polymorphisms (SNPs) located in these genes have been widely analyzed with controversial results. We analyzed a group of SNPs located in the three genes: CD28: rs3116496; CD86: rs1129055; and CTLA-4: rs231775 and rs3087243 in a cohort of 632 consecutively recruited kidney transplanted subjects. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
4
2
0
Order By: Relevance
“…Our findings suggest that CD 86 gene +1057G>A polymorphism didn`t show a statistically significant association with AR. In agreement with our results, CD 86 gene rs1129055 and CD 28 gene rs3116496 polymorphism were reported to have non-significant association with AR either in the dominant or in the recessive models 22 . However, Han et al, reviewed three studies (234 cases and 411 controls) to define the relationship between the CD86 +1057G/A polymorphism and allograft rejection and reported a significant association between CD86 +1057G/A polymorphism and reduced AR in the dominant genetic model (A/A or A/G vs. G/G) 4 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our findings suggest that CD 86 gene +1057G>A polymorphism didn`t show a statistically significant association with AR. In agreement with our results, CD 86 gene rs1129055 and CD 28 gene rs3116496 polymorphism were reported to have non-significant association with AR either in the dominant or in the recessive models 22 . However, Han et al, reviewed three studies (234 cases and 411 controls) to define the relationship between the CD86 +1057G/A polymorphism and allograft rejection and reported a significant association between CD86 +1057G/A polymorphism and reduced AR in the dominant genetic model (A/A or A/G vs. G/G) 4 .…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that AG genotype of CTLA-4 rs3087243 SNP was the most common genotype among no rejection group and proved a protective effect against AR and this finding came in agreement with the known inhibitory effect of CTLA-4 on T cell activation and so protection against kidney allograft rejection. Our combined results were similar to a cohort of 632 kidney transplant patients who showed a protection against kidney transplant rejection among carriers of the CTLA-4 +6230 G allele which is proved by detecting lower levels of soluble cytotoxic T lymphocyte antigen-4 micro RNA (sCTLA-4 mRNA) 22 . In deceased kidney transplantation, a retrospective study examining 72 deceased donor derived kidney transplant recipients who completed 6 months of follow up post transplantation, reported a significant higher incidence of CT60 A/A genotype in AR group compared with no rejection group (29.7% vs 8.6%; P = 0.035; OR = 4.51) and a higher incidence of CT60 A/G genotype in the no rejection group 27 .…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations